2012
DOI: 10.3892/ijmm.2012.934
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic response of mesenchymal stem cells to continuous mechanical strain is dependent on ERK1/2-Runx2 signaling

Abstract: Abstract. Mechanical stimuli are responsible for bone remodeling during orthodontic tooth movement. The role of mechanical stimulation in the regulation of the fate of bone mesenchymal stem cells (BMSCs) is of interest in bone regeneration and tissue engineering applications. However, the signaling pathway involved in strain-induced biochemical events in BMSCs is not well established and can be controversial. This study investigated strain-induced proliferation and differentiation of BMSCs, as well as the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…Our data showed that production of Cbfa1/Runx2 initially increased but then decreased in response to a long period of NPWT treatment. This result was consistent with the report from Huang and Rei [17], and opposite to the reports about osteogenic response of MSCs to continuous mechanical strain [16], [34]. We hypothesize that both mechanical stretch and hydrostatic pressure contribute to the osteoblastic differentiation of P-MSCs, and the cells in fibrin matrix were more sensitive to fluid-shear stress, which may play a leading role in the mechanical stimuli created by NPWT.…”
Section: Discussionsupporting
confidence: 89%
“…Our data showed that production of Cbfa1/Runx2 initially increased but then decreased in response to a long period of NPWT treatment. This result was consistent with the report from Huang and Rei [17], and opposite to the reports about osteogenic response of MSCs to continuous mechanical strain [16], [34]. We hypothesize that both mechanical stretch and hydrostatic pressure contribute to the osteoblastic differentiation of P-MSCs, and the cells in fibrin matrix were more sensitive to fluid-shear stress, which may play a leading role in the mechanical stimuli created by NPWT.…”
Section: Discussionsupporting
confidence: 89%
“…Typical 2-D substrates include tissue culture polystyrene [21], glass [145], silicone membrane [146], bone slices [147], and these substrates can also be surface-coated (e.g. with collagen, fibronectin) to study the integrated effects of cell adhesion and loading on mechanotransduction [148].…”
Section: Models Of Applied Mechanical Loadingmentioning
confidence: 99%
“…the Flexcell® line), and their application has revealed that stretching significantly changes cell behavior. For example, mechanical stretching induces osteogenic differentiation, as detected via increased expression of ALP [146, 152], Runx2 [146, 148, 152, 153], and collagen [146, 148, 153], as well as elevated calcium deposition [154, 155], even in the absence of osteogenic growth factors [156, 157]. As with physiological mechanical loading, this response is enhanced with increasing strain magnitude [153, 157].…”
Section: Models Of Applied Mechanical Loadingmentioning
confidence: 99%
“…The authors also found that this long term application of strain reduced the proliferative capacity of MSCs, supporting the notion that although short-term strains may increase proliferation, long-term strains do not appear to [7]. It has also been shown that both osteoblastogenesis and osteoclastogenesis are influenced by mechanical stimulation, showing how far reaching the effects of mechanical load are in bone formation and maintenance [30, 31]. …”
Section: The Effect Of Tensile Strain On Progenitor Cell Proliferatiomentioning
confidence: 68%
“…There are many signalling pathways that have been implicated regarding how mechanical stimulation effects osteogenesis, for example, one study shows that the onset of osteogenic differentiation following mechanical stimulation may be dependent on ERK1/2-Runx2 signalling [30]. Another study investigating human BM-MSCs following stretch, reports an induction of FosB, a member of the AP-1 family of transcription factors which regulate osteogenic differentiation and bone formation, in a time-and stretch-dependent manner [32].…”
Section: The Effect Of Tensile Strain On Progenitor Cell Proliferatiomentioning
confidence: 99%